Early Detection Counseling for Cervical Cancer in Perbarakan Village, Pagar Merbau District - Wulan, Sri; Nasution, Amanda Maulida; Livina, Meri; Harahap, Cindy Artika (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2025)
Counseling on early detection of cervical cancer is an important effort to increase public awareness and knowledge, especially Women of Childbearing Age (WUS), regarding the dangers and prevention of cervical cancer. Cervical cancer is a serious health problem that is the second leading cause of death among women with cancer. Cervical cancer is dangerous because it can cause death if not detected early. This disease damages reproductive organs, reduces quality of life, and causes pain and abnormal bleeding. In addition, treatment is expensive and carries the risk of infertility as well as psychological and social impacts for sufferers. This counseling activity was held in Perbarakan Village, Dusun 1 on Friday, May 2, 2025, at 16.00 WIB and was attended by 35 participants. The material presented in the activity included the definition of cervical cancer, risk factors, signs and symptoms, the importance of early detection, prevention methods, maintaining reproductive organ hygiene, healthy sexual relations, and the importance of HPV vaccination. Before the counseling, the level of knowledge of participants regarding cervical cancer and early detection efforts was relatively low (below 50%). However, after the activity took place, there was a significant increase in knowledge (more than 80%). The success of the activity was seen from the high enthusiasm of the participants during the discussion and question and answer sessions, which created an interactive and effective learning atmosphere. With cooperation between the community, families, and health workers, it is hoped that similar activities can continue to be carried out to reduce the incidence and mortality due to cervical cancer and create a healthy and quality generation of women.